Ethical Challenges and Considerations in AI-Driven Psychiatric Data Privacy in Brunei Bru-HIMS and BruHealth - Nehaluddin AHMAD; Lilly Suzana SHAMSU; Danish Iqbal ARIFFIN; Zheimie H. ZAMRI And Norulaziemah ZULKIFFLE (Communications of International Proceedings, 2025)
Recent statistics show a notable influx of Bruneians seeking mental health care, with 13,246 individuals accessing services over the past year, highlighting an urgent need to address how sensitive psychiatric data is managed within AI-supported health systems. As Brunei integrates AI technologies into platforms like Bru-HIMS and BruHealth, ethical concerns regarding data privacy, patient consent, and algorithmic accountability become increasingly pressing. Despite global discourse on AI ethics in healthcare, there remains a significant gap in the literature concerning how these issues manifest in smaller, developing countries with distinct socio-cultural and religious contexts like Brunei. This study seeks to fill that ,void by critically examining the ethical challenges of AI-driven health data systems, specifically in the context of psychiatric treatment. Using qualitative doctrinal research complemented by a comparative analysis of international ethical guidelines and local regulatory frameworks, the study identifies key risks associated with privacy breaches, data misuse, and the marginalisation of psychiatric patients. It also examines the regulatory readiness of Brunei’s health data ,governance in relation to AI integration.The findings reveal a mismatch between the rapid adoption of AI technologies ,and the underdeveloped legal-ethical safeguards, underscoring the need for more robust, culturally attuned data protection ,policies. This study offers recommendations for lawmakers, health authorities, and AI developers to foster responsible innovation that protects patient dignity while maintaining public trust in digital health systems.
Keywords: Artificial Intelligence (AI); AI Ethics; Data Privacy; Psychiatric.